A novel minimally invasive and versatile kyphoplasty balloon-based model of porcine spinal cord injury - Barber, Sean M.; Wolfe, Tatiana; Steele, Alexander G.; Hoffman, Kris; Hogan, Matthew K.; Frazier, Allison; Tang, Xiufeng; Sayenko, Dimitry G.; Horner, Philip J. (Frontiers in Neurology, 2024)
Introduction Spinal cord injury (SCI) animal models often utilize an open surgical laminectomy, which results in animal morbidity and also leads to changes in spinal canal diameter, spinal cord perfusion, cerebrospinal fluid flow dynamics, and spinal stability which may confound SCI research. Moreover, the use of open surgical laminectomy for injury creation lacks realism when considering human SCI scenarios. Methods We developed a novel, image-guided, minimally invasive, large animal model of SCI which utilizes a kyphoplasty balloon inserted into the epidural space via an interlaminar approach without the need for open surgery. Results The model was validated in 5 Yucatán pigs with imaging, neurofunctional, histologic, and electrophysiologic findings consistent with a mild compression injury. Discussion Few large animal models exist that have the potential to reproduce the mechanisms of spinal cord injury (SCI) commonly seen in humans, which in turn limits the relevance and applicability of SCI translational research. SCI research relies heavily on animal models, which typically involve an open surgical, dorsal laminectomy which is inherently invasive and may have untoward consequences on animal morbidity and spinal physiology that limit translational impact. We developed a minimally invasive, large animal model of spinal cord injury which utilizes a kyphoplasty balloon inserted percutaneously into the spinal epidural space. Balloon inflation results in a targeted, compressive spinal cord injury with histological and electrophysiological features directly relevant to human spinal cord injury cases without the need for invasive surgery. Balloon inflation pressure, length of time that balloon remains inflated, and speed of inflation may be modified to achieve variations in injury severity and subtype.